The Titanosaur Sauropods from the late Campanian–early Maastrichtian Allen Formation of Salitral Moreno, Río Negro, Argentina - Garcia, Rodolfo A. (2011)
Fil: Garcia, Rodolfo A. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina